1997
DOI: 10.1007/s001340050455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrocardiograms recorded with standard leads and derived from the vectorcardiographic Frank leads in high-risk patients

Abstract: Dynamic vectorcardiography (VCG) is increasingly employed for ischaemia monitoring with the use of a computerized method for recording and on-line analysis by the calculation of trend parameters. To elucidate how well the derived electrocardiogram (dECG), calculated from the VCG, compares with the simultaneously registered standard ECG (sECG), dECGs from 17 postoperative cardiac-risk patients and 36 subjects with acute myocardial infarction (AMI) were compared to sECGs, both quantitatively in leads II, III, V2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Analysis of the high-resolution vectorcardiogram (VCG) enables detection of electrical activity of individual and/or typical for patient group fragments of the cardiac muscle that presents a possibility for developing a qualitatively new diagnostic method. Comparing VCG to the standard electrocardiogram (ECG), the former shows the advantage of having better sensitivity for analysis of the repolarization process and myocardial ischemia [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the high-resolution vectorcardiogram (VCG) enables detection of electrical activity of individual and/or typical for patient group fragments of the cardiac muscle that presents a possibility for developing a qualitatively new diagnostic method. Comparing VCG to the standard electrocardiogram (ECG), the former shows the advantage of having better sensitivity for analysis of the repolarization process and myocardial ischemia [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [10,11], we have demonstrated that the circadian profile of the autonomic cardiac control in patients with CSX, is similar to the profile of healthy persons, but is different from the profiles of different patient groups with CAD. Since with CSX patients the stress test will show changes on the electrocardiogram that are strongly suggestive of ischemia, the aim of this study is to obtain CSX patterns of the VCG loops in the horizontal, frontal and right saggital planes of the Frank corrected orthogonal leads (X, Y, Z) [2] in resting state and to assess their similarity with the reference VCG loops of normal subjects.…”
Section: Introductionmentioning
confidence: 99%